Perbandingan Sistem Informasi Edukasi dan Dukungan Pasien Yang Tepat Untuk Perawatan Pasien Home Care - Renny Afriany; Samsinar Samsinar; Rudolf Sinaga (STIKES Garuda Putih, 2024)
In home care patient care, patient education and support information systems play an important role in providing appropriate information and support to patients and their families. This information system can be accessed by patients and their families anytime and anywhere, thereby increasing the effectiveness of care. There are various patient education and support information systems available on the market. Each system has its own advantages and disadvantages. Therefore, it is important to compare these systems to determine the most appropriate system for treating home care patients. From these results and discussion, it can be concluded that each platform has its own advantages and disadvantages. The best choice depends on the Home Care patient's individual preferences and specific needs. The level of ease of access, service response, and availability of complete medical information are the main factors in choosing a suitable platform to be used as a home care referral platform.